Opioid-sparing Strategies in Alloplastic Breast Reconstruction: A Systematic Review - Dustin T. Crystal, MD (Wolters Kluwer, 2021)
Introduction:. Pain and discomfort are frequently experienced following mastectomy with concomitant breast implant- or tissue expander-based alloplastic breast reconstruction (AlBR). Unfortunately, postoperative opioids have decreased efficacy in AlBR, short-term complication profiles, and are fraught by long-term dependence. This systematic review aims to identify opioid-sparing pain management strategies in AlBR. Methods:. A systematic literature search of MEDLINE, Embase, Web of Science, and Cochrane Central Register was performed in September 2018. PRISMA guidelines were followed, and the review was prospectively registered in PROSPERO (CRD42018107911). The search identified 1184 articles. Inclusion criteria were defined as patients 18 years or older undergoing AlBR. Results:. Fourteen articles were identified assessing opioid-sparing strategies in AlBR. This literature included articles evaluating enhanced recovery protocols (two), intercostal blocks (two), paravertebral blocks (four), liposomal bupivacaine (three), diclofenac (one), and local anesthesia infusion pumps (two). The literature included five randomized trials and nine cohort studies. Study characteristics, bias (low to high risk), and reporting outcomes were extensively heterogeneous between articles. Qualitative analysis suggests reduced opioid utilization in enhanced recovery after surgery (ERAS) pathways, paravertebral blocks, and use of liposomal bupivacaine. Conclusions:. A variety of opioid-sparing strategies are described for pain management in AlBR. Multimodal analgesia should be provided via ERAS pathways as they appear to reduce pain and spare opioid use. Targeted paravertebral blocks and liposomal bupivacaine field blocks appear to be beneficial in sparing opioids and should be considered as essential components of ERAS protocols. Additional prospective, randomized trials are necessary to delineate the efficacy of other studied modalities.